Studi Empiris Rasio Cepat dan Profitabilitas pada Perusahaan Manufaktur di Indonesia - Lanemey Brigitha Pandeirot; Elvis Ronald Sumanti; Andrew Christian Aseng (Society, 2022)
This study intended to test the effect of the quick ratio on manufacturing firms’ profitability in Indonesia. To measure the profitability, three dependent variables were used: Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE). Several variable controls were used: firm size, variability in net operating income, sales growth, gross domestic product growth, and leverage. A total of 158 manufacturing firms with published financial statements from 2012 to 2016 were analyzed using a regression method. It is found that quick ratio has positive effects on manufacturing firms’ NPM and ROA. However, the same effect is not found on ROE.